Creative Performance of Accounting Students in The VUCA Era: Bibliometric Analysis - Vanydyah Koesmarni; Indrawati Yuhertiana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The objective of this study is to examine and chart research subjects and puspose future research directions concerning the creative performance of accounting students. This analysis also enables scholars to identify new keywords for upcoming research areas. This literature review utilizes bibliometric analysis to examine 136 articles on creative performance in accounting students, employing the VOSviewer analysis tool version 1.6.19. the articles were sourced from ithe Scopus database accessed via Harzing’s Publish or Perish software between 2019 – 2023. The findings of this study reveal that growth of global sciientific publications on creative performance in accounting students has shown fluctuations annually. Furthermore, researches have identified new kywords that have not been extensively explored in the early to mid-2023, specifically “emotional intelligence”, “locus of control”, “self efficacy”, “interpersonal communication”, and “critical thinking”. It is anticipated that this research will provide valueable insights for further studies related to the creative performance of accounting students.